2020
DOI: 10.1111/nmo.13889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the cervical and abdominal vagus nerves in mice, pigs, and humans

Abstract: Background Vagus nerve (VN) stimulation is currently evaluated as a novel approach to treat immune‐mediated disorders. The optimal stimulation parameters, however, largely depend on the VN composition potentially impacting on its clinical translation. Hence, we evaluated whether morphological differences exist between the cervical and abdominal VNs across different species. Materials and methods The cervical and abdominal VNs of mouse, pig, and humans were stained for major basic protein and neurofilament F to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 44 publications
5
74
1
Order By: Relevance
“…It should also be noted that in nerve morphology and ultrastructure studies, it is common to quantify the largest or smallest diameter, rather than effective circular diameter; we only compared to data that used the latter metric, which is more clearly defined. Our human cervical nerve diameters (1.9 ± 0.5 mm) were smaller than most prior published data, which reported mean diameters of 3.0 mm for 71 left cervical and 3.0 mm for 68 right cervical VNs across three studies ( Verlinden et al, 2016 ; Hammer et al, 2018 , 2015 ), but 2.0 mm for 1 left and 5 right VNs in one study ( Stakenborg et al, 2020 ). All values are nonetheless consistent with the use of 2 mm or 3 mm inner-diameter cuff electrodes for clinical implanted cervical VNS ( Santos, 2004 ), although VNS can alter nerve morphology with increased intra- and peri-neural connective tissue ( Martín-Portugués et al, 2005 ).…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…It should also be noted that in nerve morphology and ultrastructure studies, it is common to quantify the largest or smallest diameter, rather than effective circular diameter; we only compared to data that used the latter metric, which is more clearly defined. Our human cervical nerve diameters (1.9 ± 0.5 mm) were smaller than most prior published data, which reported mean diameters of 3.0 mm for 71 left cervical and 3.0 mm for 68 right cervical VNs across three studies ( Verlinden et al, 2016 ; Hammer et al, 2018 , 2015 ), but 2.0 mm for 1 left and 5 right VNs in one study ( Stakenborg et al, 2020 ). All values are nonetheless consistent with the use of 2 mm or 3 mm inner-diameter cuff electrodes for clinical implanted cervical VNS ( Santos, 2004 ), although VNS can alter nerve morphology with increased intra- and peri-neural connective tissue ( Martín-Portugués et al, 2005 ).…”
Section: Discussioncontrasting
confidence: 89%
“…A nerve : total cross-sectional area of the nerve; d nerve : effective circular diameter of the nerve; # fasc: number of fascicles; d fasc : effective circular diameter of each fascicle; A endo : cross-sectional area covered by the endoneurium, i.e., area within the inner perineurial traces; A peri : cross-sectional area covered by the perineurium; A epi : cross-sectional area covered by the epineurium, where A epi = A nerve – A endo – A peri . From top to bottom, the human cervical data from literature for A nerve and d nerve are from Hammer et al (2015) (left VN), ( Hammer et al, 2015 ) (right VN), ( Verlinden et al, 2016 ) (left VN), ( Verlinden et al, 2016 ) (right VN), ( Hammer et al, 2018 ) (left VN), ( Hammer et al, 2018 ) (right VN), ( Stakenborg et al, 2020 ) (right and left VN), and the subdiaphragmatic data are from Tailai et al (1980) (anterior VN), ( Tailai et al, 1980 ) (posterior VN), ( Gravgaard, 1968 ) (anterior VN), ( Gravgaard, 1968 ) (posterior VN), ( Stakenborg et al, 2020 ) (posterior VN). The human # fasc data are from Verlinden et al (2016) (left VN), ( Verlinden et al, 2016 ) (right VN), ( Seki et al, 2014 ) (left VN), ( Seki et al, 2014 ) (right VN), ( Hammer et al, 2018 ) (left VN), ( Hammer et al, 2018 ) (right VN), ( Stakenborg et al, 2020 ) (right and left VN) at the cervical level, and ( Stakenborg et al, 2020 ) (posterior VN) at the subdiaphragmatic level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis is based on the assumption that fiber engagement and eCAP amplitude are linearly related. However, studies have shown that the distribution of nerve fibers is non-uniform within the cervical vagus nerve, even in the relatively simple rodent nerves [70,71]. Fibers that lie closer to the stimulating or recording electrode are easier to be excited or contribute more heavily to the eCAP measurements; both effects are more prominent with larger fibers.…”
Section: Limitationsmentioning
confidence: 99%